Gender differences among sagittal plane knee kinematic and ground reaction force characteristics during a rapid sprint and cut maneuver - James, C. R.; Sizer, P. S.; Starch, D. W.; Lockhart, T. E (Research Quarterly for Exercise and Sport, 2004)
Women are more prone to anterior cruciate ligament (ACL) injury during cutting sports than men. The purpose of this study was to examine knee kinematic and ground reaction forces (GRF) differences between genders during cutting. Male and female athletes performed cutting trials while force platform and video data were recorded (180 Hz). Differences (p £ .05) were observed between groups for knee flexion at contact and GRF at maximum knee flexion. Women averaged 5.8º less flexion at contact and 1.0 N·(kg·m·s-1) -1 greater GRF at maximum flexion. Knee range of motion and peak GRF variables were not significantly different, but women had greater values. Women exhibited technique characteristics believed to increase ACL injury risk, but men exhibiting similar characteristics were also observed and could also be at risk.